2022
DOI: 10.1007/s40745-022-00379-8
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Hybrid Feature-Based Phishing Websites Detection Using Machine Learning Techniques

Abstract: In this paper, we mainly present a machine learning based approach to detect real-time phishing websites by taking into account URL and hyperlink based hybrid features to achieve high accuracy without relying on any third-party systems. In phishing, the attackers typically try to deceive internet users by masking a webpage as an official genuine webpage to steal sensitive information such as usernames, passwords, social security numbers, credit card information, et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The final identified threat is the use of compromised packages, aiming to deceive the user into utilizing unintended packages. A prevalent method of exploitation is typosquatting [14], [16], [59], a technique also frequently employed in phishing websites or emails [63], [64]. Typosquatting capitalizes on human visual errors by replacing letters in the package name with visually similar but malicious alternatives.…”
Section: ) Mitre Attandck Frameworkmentioning
confidence: 99%
“…The final identified threat is the use of compromised packages, aiming to deceive the user into utilizing unintended packages. A prevalent method of exploitation is typosquatting [14], [16], [59], a technique also frequently employed in phishing websites or emails [63], [64]. Typosquatting capitalizes on human visual errors by replacing letters in the package name with visually similar but malicious alternatives.…”
Section: ) Mitre Attandck Frameworkmentioning
confidence: 99%
“…A dataset consisting of 500 web page records in total was used in the study and 0.963 accuracy was achieved. [35] proposes a data-driven approach to detect phishing websites using various machine learning classifiers, such as Decision Tree, XGBoost, Random Forest, Support Vector Machine, and Naive Bayes by implementing various numbers/types of features such as URL-based features, hyperlink-based features, and hybrid features. They developed a dataset with 6000 URLs containing 3000 legitimate URLs and 3000 phishing URLs.…”
Section: E Machine Learning Based Detection Systemsmentioning
confidence: 99%
“…In the field of cybersecurity, it might be challenged to quickly identify newly created phishing websites. To solve these challenge, the authors in [39] suggested an anti-phishing technique based on hybrid feature to extracts only clientside's features only. Additionally, the authors created a fresh dataset for tests using machine learning classification methods.…”
Section: Literature Reviewmentioning
confidence: 99%